Eksistensi Pesantren dalam Perkembangan Lingkungan Masyarakat - Asep Bunyamin (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. Pesantren is an education system that deepens the knowledge of traditional and indigenous Islamic religion that has existed along with the arrival of Islam. Cianjur Regency is known as the City of Santri. This is because there are many students and Islamic boarding schools in Cianjur District. Based on the results of interviews with coconut, Warungkondang Sub-district, that the oldest Islamic boarding school in Cianjur is Desa Jambudipa and has a role in the development of Islam in Cianjur district. So the researcher chose this place as a research case study. At the Jambudipa village, Islamic Boarding School in building an Islamic development civilization that has used a pattern of environmental management using the principle of the City of Santri in Cianjur since 1834, this pattern still cannot be used optimally due to several obstacles and problems. The village that is the location of the research study is Jambudipa Village because this village has two types of Islamic boarding schools, namely modern boarding schools and traditional boarding schools. In addition, there is a Jambudipa village Islamic boarding school that has existed since the 18th century. The purpose of this study was to identify the role of pesantren in developing the community environment around Jambudipa Village, Warungkondang District. The research methodology used in this research is descriptive approach method. In this method, From the results of the analysis, it is found that the existence of the role of pesantren in the community around Jambudipa Village, Warungkondang District, is still good in quantity, but there is a decrease in quality caused by factors, teachers and facilities. Abstrak. Pesantren merupakan sistem Pendidikan yang memperdalam ilmu agama islam tradisional dan pribumi yang telah ada seiring dengan datangnya agama islam. Kabupaten Cianjur terkenal dengan sebutan Kota Santri. Hal itu dikarenakan bayak santri dan pondok pesantren yang ada di Kabupaten Cianjur. Berdasarkan hasil observasi wawancara bersama kelapa Kecamatan Warungkondang bahwa pesantren tertua di Cianjur salah satunya di Desa Jambudipa dan memiliki peran Sehingga peneliti memilih tempat ini sebagai studi kasus penelitian. Pesantren Desa Jambudipa dalam membangun peradaban pengembangan islam yang telah menggunakan pola penataan lingkungan menggunakan prinsip Kota Santri di Cianjur ini sejak tahun 1834 akan tetapi pola ini masih belum bisa maksimal digunakan karena beberapa kendala dan permasalahan. Desa yang menjadi lokasi studi penelitian yaitu Desa Jambudipa karena di desa ini memiliki dua jenis pesantren yaitu pesantren modern dan pesantren tradisional. Selain itu adanya peantren Desa Jambudipa yang ada sejak abad 18. Tujuan penelitian ini adalah untuk mengidentifisikan Eksistensi pesantren dalam pengembangan lingkungan masyarakat sekitar Desa Jambudipa. Metodologi penelitian yang digunakan dalam penelitian ini yaitu metode pendekatan studi kasus. Pada metode ini dilakukan penjabaran mendalam bentuk kualitatif Dari hasil analisis diperoleh bahwa eksistensi Eksistensi pesantren di lingkungan sekitar masyarakat (Kasus Desa Jambudipa) ini masih baik secara kuantitas, namun adanya penurunan secara kualitas yang disebabkan oleh faktor, pengajar dan fasilitas.